สถานีวิทยุโทรทัศน์แห่งประเทศไทยช่อง 11: การบริหารจัดการ และการทำหน้าที่ของสื่อมวลชน - ชาญวิชัย, กิตติมา (Journal of Business, Innovation and Sustainability (JBIS), 2016)
งานวิจัยนี้เป็นการวิจัยในเชิงคุณภาพ (Qualitative Research) ใช้การศึกษาวิจัยเอกสาร (Documentary Research) การสังเกต (Observation) และการสัมภาษณ์เจาะลึก (In – depth Interview) จากคำถามที่ได้เตรียมไว้ เป็นเครื่องมือในการเก็บ รวบรวมข้อมูลมีวัตถุประสงค์ 1) เพื่อศึกษารูปแบบและวิธีการการบริหารจัดการแบบใหม่ของสถานีวิทยุโทรทัศน์แห่งประเทศไทย ช่อง 11 2) เพื่อศึกษาความคาดหวังและความพึงพอใจของบุคลากรต่อการบริหารจัดการแบบใหม่ 3) เพื่อศึกษารูปแบบและวิธีการสื่อสารภายในองค์กร 4) เพื่อศึกษาการทำหน้าที่สื่อมวลชนและสื่อเพื่อชุมชน และ 5) เพื่อศึกษาถึงปัญหาและอุปสรรคต่าง ๆ ในการ ทำหน้าที่สื่อมวลชน รวมถึงความพยายามในการปรับเปลี่ยนการบริหารจัดการให้มีความสอดคล้องกับการทำหน้าที่ดังกล่าว ผลการวิจัยพบว่า 1) การบริหารจัดการของสทท. 11 ยังคงเป็นระบบราชการ ที่ยังมีความล่าช้าและมีขั้นตอนซับซ้อนมากเกินไป และจากการเป็นองค์กรสื่อที่ทำงานตามระบบราชการทำให้พบประสบปัญหาและอุปสรรคมาก 2)ความคาดหวังของบุคลากรต่อ วิธีการบริหารจัดการแบบใหม่ของ สทท. 11 คือการมีอิสระในการทำงานในฐานะสื่อมวลชน และความต้องการกฎระเบียบต่าง ๆ ที่ต้องสอดคล้องกับความเป็นจริง สามารถดึงชุมชนเข้ามาเป็นแนวร่วมในการทำงาน และต้องเป็นระบบที่สามารถปรับ ค่าตอบแทนของบุคลากรให้ตรงกับความเป็นจริง 3) รูปแบบและวิธีการสื่อสารภายในองค์กร มีความเห็นต่างระหว่างกลุ่มผู้บริหาร และปฏิบัติการ โดยกลุ่มผู้บริหารระดับสูงและระดับกลาง ต้องการให้สทท. 11 ในส่วนภูมิภาคทำงานขึ้นตรงกับสทท. 11 ใน ส่วนกลาง แต่กลุ่มระดับปฏิบัติการส่วนหนึ่งมีความเห็นว่าการขึ้นตรงกับเขต (ภูมิภาค) จะมีความสะดวกและคล่องตัวกว่า 4) การทำหน้าที่สื่อมวลชน พบว่า กลุ่มผู้ให้ข้อมูลทั้ง 3 กลุ่มมีความเห็นตรงกันว่า ต้องการให้ประชาชนมาร่วมคิดร่วมทำกับสถานีฯ อย่างเป็นรูปธรรม โดยควรกำหนดให้มีคณะทำงานภาควิชาการ ทั้งภาคเอกชนและภาคประชาชนร่วมเป็นเครือข่าย เพื่อทำหน้าที่ให้ คำปรึกษา เสนอแนะ ประเมินผล และ5) ประโยชน์ที่คาดว่าจะได้รับจากการปรับเปลี่ยนการบริหารจัดการแบบใหม่ ผู้ให้ข้อมูล ต้องการให้การปรับเปลี่ยนก่อให้เกิดประโยชน์ทั้งต่อตนเอง ต่อองค์กร และต่อสังคม Television of Thailand Channel 11: An Exploratory Research of Its Managerial Approach and Performance as a National Mass Media This research has applied 3 qualitative research techniques such as documentary research, observation, and in-depth interviews to explore Television of Thailand Channel 11 in terms of its managerial approach and performance as a national mass media as stated in the following aspects: 1) a new form and managerial approach of Channel 11, 2) its personnel’s expectation and satisfaction towards the new managerial approach, 3) a form of organizational communication within Channel 11, 4) its performance as mass media and community media as well, 5) problems and difficulties against its performance and adaptation. This research has revealed 5 findings. 1) Channel 11’s employed a managerial approach attached to bureaucratic, so-called “red tape,” system which caused several problems and difficulties. 2) Hence, the Channel 11 personnel expected the concept of “freedom of the press” in working climate. Also, they wanted some practical rules which were consistent with the real situation. By this it means that to abide by those rules would encourage Channel 11 to persuade the community to work hand in hand with its officers. Moreover, with this effort, the incentives had to also be adjusted reasonably. 3) The approach of organizational communication within Channel 11 was viewed differently between two groups among top and middle management, and operational level. The former noted that they wanted Channel 11 regional network should be dependent on the Headquarter. Whereas, the latter wanted regional stations run independently due to its convenient and flexible performance. 4) In addition, within those 3 groups (top and middle management as well as operational level), they all agreed that Channel 11 in cooperation with private sector and its local audience set up a networking academic committee. 5) Also, they believed that the newly adjusted managerial approach would contribute advantages to themselves, organization, and the society. DOI: http://dx.doi.org/10.14456/becj.2014.18